(untitled) (Medico Legal Update, 2020)
A descriptive Study on Assessment of the psychological wellbeing residing in pooncheri rural community area in kancheepuram (dist.), Tamil Nadu India. The objectives are to assess psychological wellbeing of elderly people. To find out the association between levels of psychological wellbeing of elderly people and selected demographic variables of elderly people. The sampling technique was non-probability, purposive sampling technique with 111 samples of elderly people and WHO standardized psychological wellbeing scale were used to assess psychological wellbeing of elderly. The demographic variables Performa, were used to collect data. The data collection tools were validated and reliability was established. The data collection for the main study was done. The collected data was tabulated and analyzed, using descriptive and inferential statistics. Majority of elderly 71.2% had adequate, 28.8% had moderate wellbeing, There no poor wellbeing. The psychological wellbeing mean value is57.34.